Pattern of congenital anomalies at birth and their correlations with maternal characteristics in the maternity teaching hospital, Erbil city, Iraq - Sozan K. Ameen; Shahla Kareem Alalaf; Nazar P. Shabila (BMC, 2018)
Abstract Background Congenital anomalies are a worldwide problem, causing perinatal and infant deaths and postnatal physical disabilities. This study aimed to determine the pattern and associated factors of the congenital anomalies in newborns delivered at the Maternity Teaching Hospital, Erbil city. Methods All the births occurring in the labor room of the Maternity Teaching Hospital in Erbil city, Kurdistan region, Iraq between 1st April 2015 and the end of March 2016 were recorded. All babies with congenital anomalies were identified. The rate and common types of congenital anomalies were estimated. A case-control study was conducted involving all women who had babies with congenital anomalies and the same number whose babies had no congenital anomalies. Data were collected using a structured questionnaire. Results Of the 35,803 recorded births in the Maternity Teaching Hospital, Erbil, 130 women delivered babies with at least one congenital anomaly, giving a rate of 3.63/1000 deliveries. The most common area for anomalies was the central nervous system (37.7%) followed by the musculoskeletal (23.1%) and gastrointestinal systems (20.8%). There was a statistically significant association between having a child with congenital anomalies and a maternal history of previous congenital anomalies (odds ratio [OR] 59.0, 95% CI 5.74-607.0), parental consanguinity (OR 6.26, 95% CI 2.42-16.19), and history of medical disorders (OR 153.2, 95% CI 25.9-905.4). Maternal occupation and smoking did not have any influence to develop congenital anomalies (OR 0.69, 95% CI 0.12-3.97 and OR 1.22,95% CI 0.19-7.93). Conclusion Anomalies were most likely to be in the central nervous system. Maternal history of previous congenital anomalies, parental consanguinity, and history of medical disorders were the most important factors associated with congenital anomalies. This study provides baseline information for future prevention and better management of patients likely to have babies with congenital anomalies. More research is required to identify the factors responsible for the different types of congenital anomalies.